The catalytic domain of insulin-degrading enzyme forms a denaturant-resistant complex with amyloid β peptide: Implications for Alzheimer disease pathogenesis - Llovera, Ramiro Esteban (2008)
Insulin-degrading enzyme (IDE) is central to the turnover of insulin and degrades amyloid β (Aβ) in the mammalian brain. Biochemical and genetic data support the notion that IDE may play a role in late onset Alzheimer disease (AD), and recent studies suggest an association between AD and diabetes mellitus type 2. Here we show that a natively folded recombinant IDE was capable of forming a stable complex with Aβ that resisted dissociation after treatment with strong denaturants. This interaction was also observed with rat brain IDE and detected in an SDS-soluble fraction from AD cortical tissue. Aβ sequence 17-27, known to be crucial in amyloid assembly, was sufficient to form a stable complex with IDE. Monomeric as opposed to aggregated Aβ was competent to associate irreversibly with IDE following a very slow kinetics (t1/2 ∼ 45 min). Partial denaturation of IDE as well as preincubation with a 10-fold molar excess of insulin prevented complex formation, suggesting that the irreversible interaction of Aβ takes place with at least part of the substrate binding site of the protease. Limited proteolysis showed that Aβ remained bound to a ∼25-kDa N-terminal fragment of IDE in an SDS-resistant manner. Mass spectrometry after in gel digestion of the IDE·Aβ complex showed that peptides derived from the region that includes the catalytic site of IDE were recovered with Aβ. Taken together, these results are suggestive of an unprecedented mechanism of conformation-dependent substrate binding that may perturb Aβ clearance, insulin turnover, and promote AD pathogenesis.